A prototype non-invasive urodynamic test to estimate voiding reserve in normal adult males. Issue 4 (2nd October 2019) - Shoukry, Shafik; Elmissiry, Mostafa; Abulfotooh, Ahmed; Moussa, Ahmed; Mahfouz, Wally; Dawood, Waleed; Abdel-Karim, Aly; Hassouna, Mohamed
ABSTRACT: Objective : To propose a prototype non-invasive test to estimate voiding reserve in normal adult men; identifying its feasibility, limitations, and initial results. Subjects and methods : In all, 30 adult healthy male volunteers aged <40 years were included in the study. Initial free uroflowmetry was done with post-void residual urine volume (PVR) assessment using ultrasonography. The men were later asked to void into a uroflowmeter through a condom catheter attached to the glans penis and connected to an outflow tube with specific vertical heights (10, 20, 30, 40, 50 and 60 cm) on different days. The mean maximum urinary flow rate (Qmax ) and PVR at each height were compared with the Qmax and PVR at the initial free uroflowmetry. The maximum height at which the Qmax and PVR remained normal was considered the normal voiding reserve for that age group. Results : All the men completed the study without any complications. At zero level, the mean Qmax was 27.6 mL/s, which then dropped gradually to reach 17.8 mL/s at 60 cm, where still 83% of the men had a normal Qmax . The PVR was nil at zero level and started to exceed the normal range at 50 and 60 cm height (58 and 65.7 mL, respectively). So, the maximum height resistance at which the men could have a normal Qmax and normal PVR was 40 cm. Conclusions : The use of the tube height-resistance test to assess voiding reserve is feasible, non-invasive and has no complications. A 40-cm height resistance can be considered a reference level that a young adult male should be tested against to estimate his voiding reserve. Abbreviations : NPV: negative predictive value; Pdet Qmax : maximum detrusor pressure at maximum urinary flow; PPV: positive predictive value; PVR: post-void residual urine volume; ROC: receiver operating characteristic